EFEKTIFITAS PENGGUNAAN DANA CSR SEBAGAI UPAYA MENINGKATKAN AKUNTABILITAS PUBLIK PT PETROKIMIA GRESIK - Mayasari, Intan Puspita (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is conducted at PT Petrokimia Gresik. This research is meant to find out the effectiveness of CSRbudget as an effort to improve to public accountability. According to KEP-100/MBU/2002 about the TheAssessment of BUMN healty level that the method of assessment in determining the funds whether it iseffectively distributed or not can be seen from the companyâs performance, which consists of 2 performanceswhich are the effectiveness performance of funds distribution and the collectability of loan repayment from eachperformance. Their own percentage, in 2010-2012 PT Petrokimia Gresik can be said effective in implementingthe CSR program, since the score which is obtained for three years is as much as 3 points and the effectivenesspercentage of funds distribution obtains more than 90% while the collectability of loan repayment obtains morethan 70%. PT Petrokimia Gresik can be said effective and in appropriate with the public accountabilityKeywords: Effectiveness, Public Accountability, CSR.